Amperometric Screen-Printed Galactose Biosensor for Cell Toxicity Applications. (22nd January 2016) - Kanyong, Prosper; Hughes, Gareth; Pemberton, Roy M.; Jackson, Simon K.; Hart, John P.
ABSTRACT: This paper reports the development and application of a biosensor for the amperometric determination of galactose in the presence of human hepatocellular carcinoma cells with and without a hepatotoxic agent. The biosensor was fabricated by drop-coating 1.5% cellulose acetate on a 3 × 3 mm screen-printed carbon electrode followed by depositing 2 U of galactose oxidase. The electrodes dimensions were reduced to 3 × 0.5 mm before measurements. Hepatocellular carcinoma cells were utilized for in vitro toxicity testing by evaluating the effect of paracetamol on galactose uptake. The amperometric responses to galactose indicated that the inhibition of uptake was directly proportional to the concentration of paracetamol following 24 h of exposure to the hepatocellular carcinoma cells. These results demonstrate that the fabricated biosensor may be used for the real-time monitoring of cell metabolism and toxicity.